QUANTITATIVE AND QUALITATIVE ANALYSIS OF ACCOUNTING INFORMATION IN ASSESSING THE FINANCIAL POSITION OF BUSINESS ENTITIES (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the issues of assessing the financial stability of business entities. In particular, it highlights the importance of classifying assets according to their degree of liquidity and grouping liabilities based on maturity when determining solvency. Special emphasis is placed on the significance of properly structuring accounting information during the analysis process. Furthermore, it is scientifically substantiated that the presence of hard-to-liquidate resources within assets and the existence of short-term liabilities requiring prompt settlement may lead to misinterpretations, even in cases where the current solvency ratio indicates a relatively high value.